PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN FINANCIAL DISTRESS TERHADAP PENERAPAN KONSERVATISME AKUNTANSI - Efendi, Ricky Ardianto; Handayani, Susi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This research aims to obtain empirical evidence regarding the effect of profitability, firm size, and financial distress on the application of accounting conservatism. In this research, the variables consist of the independent variable and the dependent variable. The independent variables used are profitability, firm size, and financial distress. While the dependent variable used is accounting conservatism. The population chosen to be researched are companies listed on the Indonesia Stock Exchange, and included in the manufacturing industry. The observation period chosen was 2017 to 2019. The data used were financial reports obtained from the official website of the Indonesia Stock Exchange. The sampling method used purposive sampling with several defined criteria. The final data sample obtained was 297 data. The method of analysis in this research is multiple linear regression, using SPSS 23 software. The results obtained are that profitability has a negative effect on the application of accounting conservatism, financial distress has a positive effect on the application of accounting conservatism, and firm size has no effect on the application of accounting conservatism.